Fuzzy time series forecasting model based on various types of similarity measure approach / Nik Muhammad Farhan Hakim Nik Badrul Alam and Nazirah Ramli - Nik Badrul Alam, Nik Muhammad Farhan Hakim; Ramli, Nazirah (Universiti Teknologi MARA Cawangan Pahang, 2019)
Fuzzy time series(FTS) is a well-known method for forecasting the time series data in linguistic values. Recently, a few studies have used the similarity measure approach in determining the performance of the FTS forecasting model. In this paper, an FTS forecasting model based on seven intervals of equal length and trapezoidal fuzzy numbers is presented. Then, the performance of FTS forecasting model using various types of similarity measure is compared. The FTS model is implemented in the case of students’ enrollment in the University of Alabama and the unemployment rate in Malaysia. The hybrid similarity measure of geometric distance, center of gravity, area, perimeter and height gives the best performance